In Vivo Validation of the Mutant Selection Window Hypothesis with Moxifloxacin in a Murine Model of Tuberculosis - Almeida, Deepak (American Society for Microbiology (ASM), 2007)
Combination therapy is the most effective strategy to prevent emergence of resistance during tuberculosis (TB) treatment. Another strategy, albeit theoretical, is to limit the time that drug concentrations fall in the “mutant selection window” (MSW) between the MIC and the mutant prevention concentration (MPC). Drug concentrations above the MPC prevent selective amplification of resistant mutants in vitro even with a single drug exposure. The MSW concept has been validated using fluoroquinolones against Mycobacterium tuberculosis in vitro but not in vivo. Using a mouse model in which serum moxifloxacin (MXF) concentrations were maintained above the MPC, we tested whether this strategy prevents selection of MXF-resistant mutants. Beginning 2 weeks after aerosol infection with M. tuberculosis, when the mean lung log(10) CFU count was 7.9 ± 0.2, mice received either no treatment or MXF in the diet at 0.25% to approximate the conventional human dose or 1.5% to maintain serum concentrations above the MPC (8 μg/ml). After 56 days of treatment, lung CFU counts were 3.5 ± 0.8 and 0.9 ± 0.6 in 0.25% and 1.5% of the MXF-treated mice, respectively. In mice given 0.25% MXF, MXF-resistant mutants were selected by day 28 and detected in 16% (3/19) of mice tested on day 56. No selection of MXF-resistant mutants was detected in mice given 1.5% MXF. We conclude that maintaining serum concentrations of MXF above the MPC prevents selection of MXF-resistant mutants. Although this target cannot be achieved clinically with MXF, it might be possible with new fluoroquinolones with more potent activity and/or improved pharmacokinetics.